2021
DOI: 10.1111/bjir.12606
|View full text |Cite
|
Sign up to set email alerts
|

Union Membership Peaks in Midlife

Abstract: Using data from 68 countries on over 8 million respondents over forty years we show union membership peaks in midlife -usually around workers' late 40s or early 50s. In doing so we extend Blanchflower's (2007) earlier study, incorporating a further 39 countries and another decade or so of data. We also found it in every US state and the District of Columbia as well as across industries. The fact that this relationship exists in virtually every country across the world challenges a key precept in industrial rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…In contrast to recent conclusions in relation to age (Blanchflower & Bryson, 2022), differences in our findings relative to Ameri et al (2019), who find no significant unexplained differential in union coverage but lower disability-related wage inequality and lower disability gaps in job retention among union members in the United States, are suggestive of an influence of institutional context on the relationship between disability and unions. Albeit recognizing the importance of international differences in disability measurement, this is something future research across countries would be well placed to assess.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to recent conclusions in relation to age (Blanchflower & Bryson, 2022), differences in our findings relative to Ameri et al (2019), who find no significant unexplained differential in union coverage but lower disability-related wage inequality and lower disability gaps in job retention among union members in the United States, are suggestive of an influence of institutional context on the relationship between disability and unions. Albeit recognizing the importance of international differences in disability measurement, this is something future research across countries would be well placed to assess.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of the latter, we consider worker composition effects, differences in preferences for union representation and evaluations of union performance, and whether unions are associated with lower disability-related labour market inequality. The findings, therefore, contribute to, and integrate a body of evidence on, the composition and impact of union membership (see Blanchflower & Bryson, 2010, 2022 with the literature relating to disability-related labour market inequality, including disability pay gap (DPG) (Jones et al, 2006;Longhi et al, 2012) and disability employment gap (DEG) (Baumberg et al, 2015). In doing so, this article provides timely and important new evidence for government policy which aims to reduce the DEG in the UK (HM Government, 2021).…”
mentioning
confidence: 65%
“…Of note also is that Blanchflower and Bryson (2020) have found that union membership peaks in midlife. Over time there have been changes in that the level of the peak has fallen as union density rates have fallen.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the relationship between age and union membership is also non-linear (Ebbinghaus et al, 2011;Kirmanoğlu and Başlevent, 2012). Although younger employees tend to have lower probabilities of unionisation (Vandaele, 2019), Blanchflower and Bryson (2022) show that the probability of being unionised increases until an individual is in their late 40s or early 50s and then declines. This pattern holds even when controlling for birth cohort dummies.…”
Section: Determinants Of Trade Union Densitymentioning
confidence: 94%
“…Certain sectors (in particular, mining and manufacturing) also have higher unionisation rates (Kirmanoğlu and Başlevent, 2012; Visser, 2019). Employment in the public sector is also associated with a higher probability of union membership (Blanchflower, 2007; Kirmanoğlu and Başlevent, 2012) whilst larger workplaces tend to have higher unionisation rates (Ebbinghaus et al, 2011; Kirmanoğlu and Başlevent, 2012; Visser, 2019).…”
Section: Determinants Of Trade Union Densitymentioning
confidence: 99%